PONDOK PESANTREN: Lembaga Pendidikan Pembentukan Karakter - Syafe'i, Imam (Universitas Islam Negeri Raden Intan Lampung, 2017)
Islamic Boarding Schools are the forerunner of Islamic education institutions in Indonesia. The initial attendance of Islamic boarding schools was estimated from 300-400 years ago and reached almost all levels of the Indonesian Muslim community, especially in Java. After Indonesia's independence, especially since the transition to the New Order and when economic growth really increased sharply, Islamic boarding school education became more structured and the pesantren curriculum became better. For example, in addition to the religious curriculum, pesantren also offer general lessons using a dual curriculum, mone curriculum and Ministry of Religion curriculum. As an educational institution, pesantren are very concerned about the field of religion (tafaqquh fi al-din) and the formation of national character characterized by morality. The provisions of religious education are explained in the National Education Law Article 30 paragraph (4) that religious education is in the form of diniyah education, pesantren, and other similar forms. The existence of Islamic boarding schools is an ideal partner for government institutions to jointly improve the quality of education and the foundation of national character. This can be found from various phenomena that occur, such as fights between schools and distributors that are widespread and drug users among young people are rarely found they are boarding children or graduates of boarding schools.